Identifying the chaîne opératoire of club-rush (Bolboschoenus glaucus (Lam.) S.G.Sm) tuber exploitation during the Early Natufian in the Black Desert (northeastern Jordan). (February 2023) - Arranz-Otaegui, Amaia; Pedersen, Patrick Nørskov; Schmidt, Ann Frijda; Jörgensen-Lindahl, Anne; Roe, Joe; Villemoes, Johan; Pantos, George Alexis; Killackey, Kathryn
Highlights: An interdisciplinary approach is used to identify the chaîne opératoire of club-rush tuber exploitation. 20 experimental gathering and processing experiments are carried out and evaluated. Archaeological and experimental tuber assemblages are compared. How club-rush tubers were exploited by Early Natufians is determined. Abstract: Club-rush ( Bolboschoenus spp. (Asch.) Palla) is one of the most common edible wild plant taxa found at Epipaleolithic and Neolithic sites in southwest Asia. At the Early Natufian site of Shubayqa 1 (Black Desert, Jordan) thousands of club-rush rhizome-tuber remains and hundreds of fragments of prepared meals were found. The evidence indicated that the underground storage organs of this plant were recurrently used as a source of food 14, 600 years ago. To determine how Early Natufian communities gathered, processed and transformed club-rush tubers into food, we designed an interdisciplinary study that combined experimental archaeology, archaeobotany, and ground and chipped stone tool analyses. We conducted more than 50 specific experiments over three years, and based on the experimental materials produced we inferred that 1) the best season for club-rush rhizome-tuber collection in the region was spring-summer time; 2) that the primary method to harvest the plant would have been uprooting; and 3) that the most efficient approaches to obtain perfectly peeled and clean rhizome-tubers could have entailed drying, roasting and gentle grinding of the tubers. Overall, our work provides important information to reconstruct the chaîne opératoire for club-rush tuber exploitation in the past. The experimental data and modern reference datasets allow us to interpret the archaeological material found at Shubayqa 1, and start identifying some of the activities that Natufian communities in the Black Desert undertook in relation to the exploitation of this particular source of food.